Editorial - Souza, Alice De Marchi Pereira de; Mattos, Amana; Jacó Vilela, Ana Maria; Mendonça, Anderson Pereira; Mendes, Deise Maria Leal Fernandes; Ponciano, Edna Lúcia Tinoco; Degani-Carneiro, Filipe; Ribeiro, Heloisa Fernandes Caldas; Hernández, Jimena de Garay; Quadros, Laura Cristina de Toledo; et al. (Estudos e Pesquisas em Psicologia, 2021)
Alice De Marchi Pereira de Souza, Amana Mattos, Ana Maria Jacó Vilela, Anderson Pereira Mendonça, Deise Maria Leal Fernandes Mendes, Edna Lúcia Tinoco Ponciano, Filipe Degani-Carneiro, Heloisa Fernandes Caldas Ribeiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Luiz Fernando Tura, Marcos Vinicius Brunhari, Patrícia Lorena Quitério, Rosana Lazaro Rapizo, Vanessa Dordron de Pinho, Vitor Castro Gomes